Carrying Capacity Based on Ecosystem Services for Biodiversity Conservation in the Petungkriyono Essential Ecosystem Area Candidate - Nurwidya Ambarwati; Dwi Hastuti; Lies Rahayu Wijayanti Faida (Faculty of Forestry Universitas Gadjah Mada, 2023)
The Petungkriyono protected and production forests qualified for the Essential Ecosystem Area (EEA). Perhutani manages the area, covering approximately ±7,683.33 hectares, with 80% being secondary natural forests and the habitat for endangered flora and fauna. This research aimed to analyze the suitability of Petungkriyono EEA for biodiversity preservation, protection, sustainable use, and ecosystem restoration using carrying capacity based on ecosystem services (CCES). This research used a participatory approach and expert opinion with a weighting sum on land cover and landscape variables. The results showed that approximately 74.12% of the Petungkriyono AAE candidate had high and very high CCES classes and were suitable for biodiversity and area protection priorities. Meanwhile, 14.35% was in a low class and suitable for ecosystem restoration and sustainable use priorities.